2020
DOI: 10.2308/ciia-2019-501
|View full text |Cite
|
Sign up to set email alerts
|

Data Visualization in Local Accounting Firms: Is Slow Technology Adoption Rational?

Abstract: We survey highly-experienced professionals from local accounting firms regarding the adoption of and perceived benefits from data visualization in audit practice. Although the majority of respondents have minimal experience with data visualization, local-firm partners have positive perceptions regarding the value that visualization can have on audit quality and client-related benefits. These perceptions are affected by visualization technology usage: perceived audit quality benefits increase with usage but cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…Some UK participants revealed that advanced data visualisation will assist external auditors to better communicate the outcomes of the audit and the content of the audit report. This finding is consistent with the Buchheit et al (2020) study that found local-firm partners have positive perceptions regarding the value that advanced data visualisation can have on audit quality and client-related benefits. Any increased level of communication improves client and auditor interactions as it further conveys how these actors carry and (re)produce rules (Element 3 of the framework).…”
Section: Research Findingssupporting
confidence: 91%
“…Some UK participants revealed that advanced data visualisation will assist external auditors to better communicate the outcomes of the audit and the content of the audit report. This finding is consistent with the Buchheit et al (2020) study that found local-firm partners have positive perceptions regarding the value that advanced data visualisation can have on audit quality and client-related benefits. Any increased level of communication improves client and auditor interactions as it further conveys how these actors carry and (re)produce rules (Element 3 of the framework).…”
Section: Research Findingssupporting
confidence: 91%
“…Prior literature describes some of the changes to the accounting and auditing profession due to the use of data analytics (Cao et al 2015; Schneider et al 2015; Vasarhelyi et al 2015; Warren et al 2015; Richins et al 2017; Beaulieu 2020; Buchheit et al 2020). For example, Krahel and Titera (2015, 411) describe the technological advances that can “enable faster and more articulate data collection and transmission” and can improve costing, present value calculations, and estimates.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…However, this desire by auditors to generate client insights to demonstrate their value should not be the main driving factor for adopting emerging technologies. Buchheit et al (2020) surveyed 31 US audit partners and one manager who audited private companies. Results suggest that client complexity is central to technology adoption.…”
Section: Influence Of Audit Client On Auditor's Adoption Of Emerging ...mentioning
confidence: 99%